EFFETS DU REENTRAINEMENT AEROBIE SUR L’AMELIORATION DES INDICES DE LA PERFORMANCE PHYSIQUE EN READAPTATION CARDIAQUE CHEZ LES CORONARIENS - Said Aissa Khelifa; Said Aissa Samira (European Scientific Journal, ESJ, 2014)
This study was conducted in collaboration with the Department of Sport Medicine at EHS Dr. MAOUCHE, Algiers. It intends to report the first experience of Cardiac Rehabilitation in Algeria This is a retrospective study to evaluate the relationship of the effects of retraining on aerobic performance indices in cardiac rehabilitation in Coronary. The analysis covered 158 cases of patients with multiple risk factors: HTA, Tobacco, Diabetes and Dyslipidemia. And the program whose parameters are evaluated (workload, Heart Rate and duration of the effort) is spread over 20 sessions (3 sessions / week), nearly 50% of the max power of the test, withincrementsfrom 5 to10 Watt, depending on tolerance and respiratory capacity beforer eaching the frequency thres holdcalculated, usually between 60-80% FMT. The analysis and interpretation of study results have shown better improvement in overall physical capacity of patients, led by the three parameters evaluated for this purpose. If the study showed the effectiveness of cardiac rehabilitation in the positive development of the morbidity and mortality of patients and its importance in the developpment and improved indexes of physical capacity and reducing risk factors, it still remains that this discipline, considered that an important part of the treatment in coronary heart disease, appears below what it should be in our country, notwithstanding all that has been shown by various studies noting its effectiveness and importance.